Primary sinonasal ameloblastoma: A case illustration and systematic review of literature - Sampurna Raha; Rajiv S. Desai; Pankaj M. Shirsat; Shivani P. Bansal; Pooja Prasad; Ankush P. Jain; Poorvashree P. Bobade (Oral Oncology Reports)
Primary sinonasal ameloblastoma (SNA) arising from sinonasal tract is very rare with few cases reported in the literature. When faced with this clinical challenge, there is currently a paucity of evidence available in the literature for the optimal diagnosis and management of patients. The present systematic review analyses the clinicopathology, complications, recurrence rate, survival, and outcomes following the management of SNA and compared with gnathic ameloblastoma (GA). Also, a case of SNA that reported to our department was included in the present study. The electronic search process was conducted on PubMed-Medline, Embase, and Scopus. Twenty-seven publications with 59 reported cases were found to meet the eligibility criteria. Quality assessment of the case reports and series was also done. The age of included cases ranged from 14 to 81 years (mean age of 56.8 years) with male to female ratio of 2.5:1. The majority of patients had nasal obstruction (n = 46). Most common histological variant of SNA was plexiform with prevalence rate of 54 %. There were six SNA-related deaths in the included studies. Data from included studies suggest that SNAs histologically resemble GA, but have different clinical presentation, immunohistochemistry (IHC) and outcomes. This review suggests that SNA is poorly understood. In-depth analysis and follow-up of the reported cases should be performed to diagnose the disease early so that clinicians can provide adequate treatment to the patients. Also, the need for more studies on IHC and advanced molecular techniques for BRAFv600e and SMO mutational status was proposed for better understanding of the lesion.